WAKTU POTENSIAL APLIKASI MIKORIZA DAN Trichoderma spp. PADA MEDIUM GAMBUT UNTUK MENINGKATKAN PERTUMBUHAN SEMAI GAHARU (Aquilaria malaccensis Lamk.) - Nafiah, M. Ali; Mardhiansyah, M.; Oktorini, Yossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Aquilaria malaccensis is one of the plants used for peatland restoration activities. Provision of quality A.malaccensis seeds is needed in conservation activities. To get a good quality of A.malaccensis must use proper cultivation techniques. Mycorrhizae and Trichoderma spp. can improve seedling growth and suppresses pathogenic. Application of mycorrhizae and Trichoderma spp. are on of the success techniques of cultivation, but need to know the potential time to apply. For this reason, this research was conducted to determine the potential time application of mycorrhizal and Trichoderma spp. to increase seddling growth. This research used a completely randomized design (CRD), which consist of 5 treatmens, 10 replications and each replication consisted of 1 seedling. The treatments used were : T1 = Trichoderma spp. on S-5 and mycorrhiza on S-1, T2 = Trichoderma spp. on S-3 and mycorrhiza on S-1, T3 = Trichoderma spp. and mycorrhiza on S-1 , T4 = Trichoderma spp. on S-1 and mycorrhiza on S-3, T5 = Trichoderma spp. on S-1 and mycorrhiza on S-5, where S = seedlings were transferred to polybags after treatment. The parameters measured were seedling survival percent, seedling height increase, seedling diameter increase, plant dry weight, and root canopy ratio. The results of this research that the application of Trichoderma spp. in 5 days before the seedling were transferred to polybags and mycorrhizae 1 day before the seedlings were transferred to polybags showed the best result for the growth of A.malaccensis seedlings with seedling height increase is 5,13 cm, plant dry weight is 1,14 g and top-root ratio is 3,09. Keywords : Aquilaria malaccensis, mycorrhizae, Trichoderma spp., peat medium